Knowledge: disease process in patients undergoing hemodialysis - Jeysse Karla de Araújo Ferreira; Natália Ramos Costa Pessoa; Nayana Pereira Pôrto; Laís Nóbrega Mendes Santos; Ana Luisa Brandão de Carvalho Lira; Cecília Maria Farias de Queiroz Frazão (Investigación y Educación en Enfermería, 2018)
Objective. To identify the relationship between socioeconomic variables and nursing outcome indicators Knowledge: disease process.